267. Viral Respiratory Infections in Children with Neuromuscular Disease and Chronic Lung Disease Hospitalized in the Pediatric Intensive Care Unit and Associated Antibiotic Use. (26th November 2018) - Shah, Nida; Scardina, Tonya; Kociolek, Larry; Patel, Sameer
Abstract: Background: Viral respiratory infections (VRIs) cause significant morbidity in children with neuromuscular disease (NMD) and chronic lung disease (CLD). Antibiotics may be prescribed to children with NMD and/or CLD during hospitalizations in the pediatric intensive care unit (PICU) due to concerns of bacterial coinfection or superinfection. The purpose of this study was to describe the bacteriologic features of these VRIs and associated antibiotic use. Methods: From May 2012 to April 2015, we identified children with NMD and/or CLD who were hospitalized in the PICU and had a respiratory virus identified by multiplex PCR. Case patients were those with CLD and/or NMD, while control patients were without these conditions. Patients with immunodeficiency, congenital heart disease, and those with positive bacterial cultures at sterile body sites, or bacterial infections identified by multiplex PCR were excluded. Virus types, bacterial respiratory culture results, peripheral WBC, X-ray findings, and receipt of antibiotics were compared between the two groups. Results: There were 104 infections among cases and 300 among controls. The most common viruses were rhinovirus/enterovirus (188, 47%), respiratory syncytial virus (91, 23%), and influenza (34, 8%). Cases were more likely to have a positive Gram stain from respiratory culture (44% vs. 10%, P < 0.01), respiratory WBC count >25 (26% vs. 9%, P < 0.01), and growth of nonrespiratory flora (46% vs. 9%, P < 0.01); but did not differ in proportion with peripheral WBC count >15 (16% vs. 21%, P = 0.43), or proportion with >60% neutrophils or >10% bandemia (54% vs. 41%, P = 0.05), or presence of an infiltrate (39% vs. 34%, P = 0.45). Proportion of patients treated for >5 days of antibiotics did not differ between the two groups (38% vs. 33%, P = 0.40). Conclusion: Broad-spectrum antibiotic use during VRI was common among patients with and without CLD and/or NMD. Though laboratory features differed between the two groups, antibiotic use was similar. Disclosures: L. Kociolek, Alere/Techlab: Investigator, Research support S. Patel, Merck: Grant Investigator, Grant recipient and Research grant Pfizer: Grant Investigator, Research grant